Lecturer's comments on students' Lab Work 1 (SGP 3113) Academic Session 2008/09. - Mar Iman, Abdul Hamid (2008)
Containings comments on Questions 1 & 2 of student's Lab Work 1 and examples of suggested answers pertaining the both questions.